Does counting species count as taxonomy? On misrepresenting systematics, yet again - de Carvalho, María Rosa (2014)
Recent commentary by Costello and collaborators on the current state of the global taxonomic enterprise attempts to demonstrate that taxonomy is not in decline as feared by taxonomists, but rather is increasing by virtue of the rate at which new species are formally named. Having supported their views with data that clearly indicate as much, Costello et al. make recommendations to increase the rate of new species descriptions even more. However, their views appear to rely on the perception of species as static and numerically if not historically equivalent entities whose value lie in their roles as "metrics". As such, their one-dimensional portrayal of the discipline, as concerned solely with the creation of new species names, fails to take into account both the conceptual and epistemological foundations of systematics. We refute the end-user view that taxonomy is on the rise simply because more new species are being described compared with earlier decades, and that, by implication, taxonomic practice is a formality whose pace can be streamlined without considerable resources, intellectual or otherwise. Rather, we defend the opposite viewpoint that professional taxonomy is in decline relative to the immediacy of the extinction crisis, and that this decline threatens not just the empirical science of phylogenetic systematics, but also the foundations of comparative biology on which other fields rely. The allocation of space in top-ranked journals to propagate views such as those of Costello et al. lends superficial credence to the unsupportive mindset of many of those in charge of the institutional fate of taxonomy. We emphasize that taxonomy and the description of new species are dependent upon, and only make sense in light of, empirically based classifications that reflect evolutionary history; homology assessments are at the centre of these endeavours, such that the biological sciences cannot afford to have professional taxonomists sacrifice the comparative and historical depth of their hypotheses in order to accelerate new species descriptions.